2003
DOI: 10.1046/j.1460-9568.2003.02484.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurons with distinctive firing patterns, morphology and distribution in laminae V–VII of the neonatal rat lumbar spinal cord

Abstract: It is generally accepted that neurons in the ventral spinal grey matter, a substantial proportion of which can be regarded as constituents of the spinal motor apparatus, receive and integrate synaptic inputs arising from various peripheral, spinal and supraspinal sources. Thus, a profound knowledge concerning the integrative properties of interneurons in the spinal ventral grey matter appears to be essential for a fair understanding of operational principles of spinal motor neural assemblies. Using the whole c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
20
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 28 publications
7
20
0
Order By: Relevance
“…It is noteworthy that a similar classification of firing patterns of ventral interneurons (with a strong preponderance of tonic cells) (Szucs et al, 2003;Theiss and Heckman, 2005) has been reported for newborn spinal cord preparations, indicating that the observed differences were not caused by culturing conditions.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…It is noteworthy that a similar classification of firing patterns of ventral interneurons (with a strong preponderance of tonic cells) (Szucs et al, 2003;Theiss and Heckman, 2005) has been reported for newborn spinal cord preparations, indicating that the observed differences were not caused by culturing conditions.…”
Section: Resultssupporting
confidence: 74%
“…Such changes occurred in coincidence with the critical transformation of spontaneous activity from bursting to sporadic discharges (Whelan, 2003;Rosato-Siri et al, 2004). Previous studies reported similar neuronal firing classes in the ventral horn of the postnatal rodent spinal cord, with phasic versus tonic (or repetitive) cells distributed in a comparable proportion (Szucs et al, 2003;Theiss and Heckman, 2005).…”
Section: K(erg) Contributes To Spike Adaptation In Gabaergic Internsupporting
confidence: 65%
See 2 more Smart Citations
“…The similar firing pattern has been reported in rat spinal neurons in ventral horn (Szucs et al 2003;Theiss and Heckman 2005;Theiss et al 2007), superficial horn (Prescott and De Koninck 2002), and deep dorsal horn (Hochman et al 1997). In response to a depolarizing step current, neurons of type 1 elicited only one to two spikes (Fig.…”
Section: Three Types Of Egfpϩ Neuronssupporting
confidence: 81%